The Rise of the Novel - Seager, Nicholas ca. 20./21. Jh (Palgrave Macmillan, 2012)
This guide explores the dominant methodologies, theories and debates surrounding the emergence of the novel during the eighteenth century. Covering key criticism on authors such as Defoe, Fielding, Richardson and Austen, the emphasis is on how critical work is interrelated, allowing readers to discern trends in the critical conversation
Description based on publisher supplied metadata and other sources
Keywords: Geschichte 1700-1800; English fiction - 18th century - History and criticism; Englisch; Romantheorie; Roman